Unpacking the organisational diversity within the collaborative economy: The contribution of an analytical framework from social enterprise theory - Lambert, Louise; Dedeurwaerdere, Tom; Nyssens, Marthe; Severi, Elisabetta; Brolis, Olivier (Ecological economics, 2019)
The field of the collaborative economy is characterized by a wide spectrum of sustainability oriented grassroots initiatives such as cooperatives, social businesses, associations and informal initiatives. However, many of these organisations are facing isomorphic pressures from the purely for profit organisational models and lack institutional support. For the further development of these grassroots initiatives, it is therefore important to better understand the organisational models that allow them to maintain a strong social mission in spite of these pressures. To this purpose, this paper develops a hierarchical cluster analysis of 50 collaborative economy initiatives operating in the Region of Brussels Capital. The analysis shows the existence of four main clusters of enterprises operating in the Brussels Region: foreign for-profit enterprises, start-ups, citizen initiatives and partnership social enterprises. Each of these clusters is characterized by a specific combination of analytical features such as the mission, the governance structure, the legal form and the type of economic resource mobilisation. On this basis, the paper explores the likely organisational trajectories of these clusters in the collaborative economy and the various institutional strategies that can strengthen the recognition and support for the sustainability oriented grassroots initiatives.